PENERAPAN MODEL PEMBELAJARAN BAMBOO DANCING UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS IV SDN 229 INPRES CAMBAYA KABUPATEN MAROS - afriandini; Alannasir, Wahyullah; Hamzah, Rahma Ashari (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Afriandini, 2023. Application of IPS Learning Outcomes Through the Bamboo Dancing Learning Model for Grade IV Students at SDN 229 Inpres Cambaya, Maros Regency. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Islamic University of Makassar. Supervised by Wahyullah Alannasir and Rahma Ashari Hamzah. This study aims to find out: (1) what is the description of the bamboo dancing learning model for fourth grade students in social studies at SDN Inpres Cambaya, Maros Regency. (2) application of the bamboo dancing learning model to improve student learning outcomes in social studies class IV SDN 229 Inpres Cambaya, Maros Regency. The approach used is a qualitative approach and a type of classroom action research (CAR), which consists of 2 cycles, where each cycle consists of 2 meetings with four stages, namely planning, implementing, observing, and reflecting. The focus of this research is the application of the bamboo dancing learning model and social studies learning outcomes for fourth grade students. The subjects of this study were teachers and fourth grade students at SDN 229 Inpres Cambaya, Maros Regency, totaling 23 students. Data collection uses the format of observation, tests, and documentation. The data analysis used is qualitative.Based on the results of observations after the implementation of the bamboo dancing learning model in the teaching activities of cycle I teachers were categorized as poor and cycle II was categorized as good. Student learning activities in cycle I are categorized as less and cycle II is categorized as good. Social studies learning outcomes for class IV students in cycle I were in the less category, while in cycle II the social studies learning outcomes for class IV students had increased to a good category. The application of the bamboo dancing learning model in social studies learning can improve social studies learning outcomes for fourth grade students at SDN 229 Inpres Cambaya, Maros Regency. Keywords: Bamboo Dancing Learning Model, IPS Learning Outcomes